Analisis dan Visualisasi Tingkat Kelulusan Mahasiswa Menggunakan Algoritma K-Means Clustering dan Silhoutte Score Berdasarkan Asal Daerah - Jermias Victor Manuhutu; Yoakhina Nicole Makaruku; Daniel Halauwet (STMIK Banjarbaru, 2026)
Academic achievement of graduates serves as a key indicator of higher education quality and graduates’ readiness to enter the workforce. This study examines the Christian Religious Education Study Program at the State Christian Institute of Ambon (IAKN Ambon) during the 2010–2020 period, focusing on the influence of students’ district of origin on graduation rates and Grade Point Average (GPA). Employing a descriptive quantitative approach based on secondary data, the analysis was conducted using descriptive statistics and the K-Means clustering method, with the optimal number of clusters evaluated through the silhouette score. The findings reveal a concentration of students from several major districts, including Central Maluku, Ambon City, and West Seram Regency. Four performance clusters were identified: high-performing, moderate-performing, challenging, and low-performing/no graduates. An Average Silhouette Score of 0.77 indicates good cluster quality and strong separation among groups. The study highlights disparities in academic achievement based on students’ geographical origins, suggesting the need for more targeted interventions and stronger collaboration with students’ home districts to improve academic success and graduation outcomes.Keywords: Academic Performance; District of Origin; Graduation Rate; K-Means Clustering; Silhouette ScoreAbstrakPrestasi akademik lulusan menjadi indikator utama mutu pendidikan tinggi dan kesiapan lulusan menghadapi dunia kerja. Penelitian ini mengkaji Program Studi Pendidikan Agama Kristen (PAK) Institut Agama Kristen Negeri Ambon periode 2010–2020, dengan fokus pada pengaruh asal kabupaten terhadap tingkat kelulusan dan IPK. Menggunakan pendekatan kuantitatif deskriptif berbasis data sekunder, analisis dilakukan melalui statistik deskriptif dan metode K-Means clustering, dengan evaluasi jumlah klaster menggunakan silhouette score. Hasil menunjukkan konsentrasi mahasiswa pada beberapa kabupaten utama seperti Maluku Tengah, Kota Ambon, dan Seram Bagian Barat. Ditemukan empat klaster kinerja, yaitu tinggi, moderat, menantang, dan rendah/tanpa lulusan. Nilai Average Silhouette Score sebesar 0,77 menunjukkan kualitas klaster yang baik. Studi ini mengungkap adanya perbedaan capaian akademik berdasarkan asal daerah, sehingga diperlukan intervensi yang lebih terarah serta kerja sama dengan daerah asal mahasiswa untuk meningkatkan keberhasilan studi.Kata kunci: Asal Kabupaten; Clustering: K-Means; Silhoutte Score; Tingkat Kelulusan